(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Individuality and identity have been the twin aspects that define a human being. The authors of young adult fiction are fond of exploring this aspect in teenagers as that age group overflows with curiosity and surprises. Teenagers like Peter Pan do not wish to grow into adults and he is not the only one with that wish in literature. J. D. Salinger is an American novelist, who takes the readers into the mindscape of one such ordinary teenager named Holden Caulfield in his renowned novel, The Catcher in the Rye (1951). Holden’s angst, turmoil, and attempts to handle the “phoniness” of the adult world while he becomes a part of it, become the issue of interest that promotes the researcher to study him using Marcia’s Identity Status Theory. The findings unfold in this research article with great earnestness.